Soft X-ray imaging of thick carbon-based materials using the normal incidence multilayer optics - Artyukov, I. A.; Feschenko, R. M.; Vinogradov, A. V.; Bugayev, Ye. A.; Devizenko, O. Y.; Kondratenko, V. V.; Kasyanov, Yu. S.; Hatano, T.; Yamamoto, M.; Saveliev, S. V. (Elsevier Ltd, 2010)
The high transparency of carbon-containing materials in the spectral region of “carbon window” (∼4.5–5 nm) introduces new opportunities for various soft X-ray microscopy applications. The development of efficient multilayer coated X-ray optics operating at the wavelengths of about 4.5nm has stimulated a series of our imaging experiments to study thick biological and synthetic objects. Our experimental set-up consisted of a laser plasma X-ray source generated with the 2nd harmonics of Nd–glass laser, scandium-based thin-film filters, Co/C multilayer mirror and X-ray film UF-4. All soft X-ray images were produced with a single nanosecond exposure and demonstrated appropriate absorption contrast and detector-limited spatial resolution. A special attention was paid to the 3D imaging of thick low-density foam materials to be used in design of laser fusion targets
Keywords: soft X-ray microscopy; carbon window; X-ray multilayer mirror; laser plasma